2007
DOI: 10.1111/j.1574-6968.2007.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The coupling ion in the methanoarchaeal ATP synthases: H+vs. Na+in the A1AoATP synthase from the archaeonMethanosarcina mazeiGö1

Abstract: To establish a system to analyze ATP synthesis by the archaeal A(1)A(o) ATP synthase and to address the nature of the coupling ion, the operon encoding the A(1)A(o) ATP synthase from the mesophile Methanosarcina mazei Gö1 was cloned in an expression vector and it was expressed in the F(1)F(o) ATP synthase-negative mutant Escherichia coli DK8. Western blot analyses revealed that each of the subunits was produced, and the subunits assembled to a functional, membrane-embedded ATP synthase/ATPase. ATP hydrolysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Further, the A 1 A 0 ATPase/synthases studied among the members of the groups Methanobacteriales/Methanococcales have clearly been shown to pump Na + (McMillan et al, 2011;Mulkidjanian et al, 2008). In contrast, the cytochrome-containing methanogens in the Methanosarcinales have Mtr complexes, but also have steps that pump protons (Schlegel & Müller, 2013;Thauer et al, 2008), and evidence has favoured H + pumping by the ATPases in these organisms (Müller et al, 1999;Pisa et al, 2007). More recently, it was demonstrated that the A 1 A 0 archaeal ATPase/synthase in Methanosarcina acetivorans is 'promiscuous', pumping either Na + or H + (Schlegel et al, 2012) with both ions possible at neutral pH, especially at seawater salinity of 0.4 M Na + , whereas only protons were pumped at pH 5.…”
Section: Adaptation To High Proton Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the A 1 A 0 ATPase/synthases studied among the members of the groups Methanobacteriales/Methanococcales have clearly been shown to pump Na + (McMillan et al, 2011;Mulkidjanian et al, 2008). In contrast, the cytochrome-containing methanogens in the Methanosarcinales have Mtr complexes, but also have steps that pump protons (Schlegel & Müller, 2013;Thauer et al, 2008), and evidence has favoured H + pumping by the ATPases in these organisms (Müller et al, 1999;Pisa et al, 2007). More recently, it was demonstrated that the A 1 A 0 archaeal ATPase/synthase in Methanosarcina acetivorans is 'promiscuous', pumping either Na + or H + (Schlegel et al, 2012) with both ions possible at neutral pH, especially at seawater salinity of 0.4 M Na + , whereas only protons were pumped at pH 5.…”
Section: Adaptation To High Proton Concentrationsmentioning
confidence: 99%
“…Organisms with experimental evidence supporting sodium-driven ATPases are shown in bold blue and include: Methanococcus jannaschii (Morsomme et al, 2002), Methanococcus voltae (Dybas & Konisky, 1992), Methanobacterium thermoautotrophicum (Schönheit & Perski, 1983) and Methanobrevibacter ruminatum (McMillan et al, 2011). Organisms with experimental evidence supporting proton-driven (or sodium/proton-driven) ATPases are shown in bold red and include: M. mazei Gö1 (Becher & Müller, 1994;Pisa et al, 2007), Methanosaeta thermophila (Inatomi et al, 1993) and M. barkeri (Blaut & Gottschalk, 1984;Müller et al, 1999). M. acetivorans C2A was recently shown to have a sodium-proton driven ATPase (Grüber et al, 2014;Schlegel & Müller, 2013) and the residues considered crucial to being allowing binding of both ions are indicated in bold, as are the corresponding amino acids in the M. boonei sequence directly above.…”
Section: Adaptation To High Proton Concentrationsmentioning
confidence: 99%
“…The specific activity of ATP hydrolysis in membranes of M. ruminantium M1 was low, 0.080 Ϯ 0.009 units/mg protein, but comparable with the ATPase activity of other A 1 A o enzymes (8,(32)(33)(34)(35). The ATPase activity of M1 membrane vesicles was stable at 4°C for up to 5 days, and activity declined after this point (data not shown).…”
Section: Growth Of M Ruminantium M1 On H 2 and Co 2 Is Dependent On mentioning
confidence: 59%
“…A noteworthy feature of the c subunit in methanogen A 1 A o -ATP synthases is the presence of a sodium ion-binding signature (11), even in proton-coupled enzymes (8). The natural environment of a methanogen will be a major factor in determining the ion specificity of the A-type enzyme for ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation